Induction of variability through mutagenesis in neelayamari (Indigofera tinctoriaL.) - Kumanan E (Department of Plant Breeding and Genetics, College of Agriculture, 2009)
The study entitled “Induction of variability through mutagenesis in neelayamari (Indigofera tinctoria L.)” was carried out in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during the period 2006-2008, with the objective of inducing variability for higher biomass yield and indigotin content in leaves.